2017
DOI: 10.1186/s12935-017-0426-6
|View full text |Cite
|
Sign up to set email alerts
|

Pepsinogen C expression, regulation and its relationship with cancer

Abstract: Pepsinogen C (PGC) belongs to the aspartic protease family and is secreted by gastric chief cells. PGC could be activated to pepsin C and digests polypeptides and amino acids, but as a zymogen PGC’s functions is unclear. In normal physiological conditions, PGC is initially detected in the late embryonic stage and is mainly expressed in gastric mucosa. The in situ expression of PGC in gastric mucosa is decreased considerably in the process of superficial gastritis → atrophic gastritis → gastric cancer (GC), pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 82 publications
1
30
0
Order By: Relevance
“…Our previous results also indicated that the expression level of PGC gradually declined during SG‐AG‐GC progression 13. Melle et al14 also found that PGC was obviously reduced in gastric cancer tissue by ProteinChip Arrays and SELDI‐TOF MS. As a negative marker, PGC has demonstrated important value in the screening, diagnosis, and prognosis of gastric cancer 15, 16…”
Section: Introductionmentioning
confidence: 99%
“…Our previous results also indicated that the expression level of PGC gradually declined during SG‐AG‐GC progression 13. Melle et al14 also found that PGC was obviously reduced in gastric cancer tissue by ProteinChip Arrays and SELDI‐TOF MS. As a negative marker, PGC has demonstrated important value in the screening, diagnosis, and prognosis of gastric cancer 15, 16…”
Section: Introductionmentioning
confidence: 99%
“…3d). Notably, the IM + CK organoids had significantly lower levels of SATB2 20 , Albumin (ALB), and Pepsinogen C (PGC) 39 expression compared with the CK + DCI HIOs (and IM + CHIR), suggesting that the IM + CK condition results in HIOs that are more homogenous and express markers specific to intestinal lineages, while preventing the emergence of hepatic and gastric lineages (Supplementary Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…The advantage of this approach is that many different foreign domains may be fused to a target protein to increase its expression level or solubility and then be removed after expression in vivo, thereby allowing production of a target protein without any extra foreign domains. This strategy has been widely used for the production of many endogenous proteins, including growth factors and cytokines in animal cells as well as proteases such as pepsin and trypsin (Shi et al, 2011;Kim et al, 2011;Shen et al, 2017). These proteins are expressed as preproproteins and then converted to their functional form via proteolytic processing.…”
Section: Discussionmentioning
confidence: 99%